2008
DOI: 10.1097/mpg.0b013e31815a5f2c
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Colonization of a Lactobacillus plantarum Synbiotic Preparation in the Neonatal Gut

Abstract: The synbiotic preparation colonized quickly after 3 days of administration and the infants stayed colonized for several months after therapy was stopped. There was an increase in bacterial diversity and gram-positive organisms and a reduction of gram-negative bacterial load in the treatment group. Because a combination preparation was used, it is difficult to specifically attribute the colonization to either the probiotic or prebiotic component in this study. Larger efficacy trials are warranted to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 54 publications
0
66
1
3
Order By: Relevance
“…85 A double-blind randomized controlled trial (RCT) with 31 infants showed that L. plantarum , when administered in a synbiotic combination with oligofructose, successfully colonized 100% of infants at 2 months and 32% at 6 months after a 1-week administration. 86 Another recent RCT examined 925 infants at risk for allergic disorders and found that daily administration of a 4-species probiotics mixture, combined with GOS, reduced antibiotic prescriptions and respiratory infections. 87 These studies suggest that effective combinations of probiotics and prebiotics result in sustainable changes in microbial composition and benefits for the human host.…”
Section: Lessons From Prebiotics and Synbioticsmentioning
confidence: 99%
“…85 A double-blind randomized controlled trial (RCT) with 31 infants showed that L. plantarum , when administered in a synbiotic combination with oligofructose, successfully colonized 100% of infants at 2 months and 32% at 6 months after a 1-week administration. 86 Another recent RCT examined 925 infants at risk for allergic disorders and found that daily administration of a 4-species probiotics mixture, combined with GOS, reduced antibiotic prescriptions and respiratory infections. 87 These studies suggest that effective combinations of probiotics and prebiotics result in sustainable changes in microbial composition and benefits for the human host.…”
Section: Lessons From Prebiotics and Synbioticsmentioning
confidence: 99%
“…Die Ergebnisse der Anwendung von (unterschiedlichen) Probiotika zur Präventi-on der NEC auf der Basis aktueller Daten lassen sich folgendermaßen skizzieren [7,15,16,18,32,35,39,44,48,57]: …”
Section: Resümeeunclassified
“…"Prebiotics" are 'non-digestible food ingredients that beneficially affect the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon, thus having the potential to improve host health 4 . Thus prebiotics enhance the survival of endogenous probiotic organisms 5,6 . The food ingredients most likely to meet these criteria at present are oligosaccharides (including inulin) and their derivatives, the fructo-oligosaccharides 7,8 .…”
Section: Prebiotics and Symbioticsmentioning
confidence: 99%